Type D Personality and Coronary Plaque Vulnerability in Patients With Coronary Artery Disease: An Optical Coherence Tomography Study. Issue 5 (June 2016) - Wang, Yini; Zhao, Zhenjuan; Gao, Xueqin; Li, Ling; Liu, Guojie; Chen, Wei; Xing, Lei; Yu, Bo; Lin, Ping
ABSTRACT: Objective: To investigate the association between Type D personality and higher incidence of major adverse cardiac events, we used in vivo optical coherence tomography (OCT) to evaluate the association between Type D with coronary plaque characteristics. Methods: A total of 109 patients who had culprit coronary plaque (s) were included in the study. The Type D construct was analyzed using both the categorized and the continuous approaches. Plaque vulnerability of culprit lesions was measured by OCT. Results: After adjusting for demographic and clinical factors, multivariate analysis demonstrated that Type D was associated with lipid plaque (odds ratio [OR] = 4.87, 95% confidence interval [CI] = 1.41–11.14, p = .025), thin cap fibroatheroma (OR = 3.84, 95% CI = 1.36–10.85, p = .011), and fibrous cap thickness ( β = −1.43, standard error = 0.04, p = .001) analyzed by categorical approach. When analyzing Type D as continuous variable, the negative affectivity component was significantly related to plaque vulnerability, including lipid plaque (OR = 3.43, 95% CI = 1.23–9.52, p = .018), thin cap fibroatheroma (OR = 2.20, 95% CI = 1.10–4.40, p = .026), and fibrous cap thickness ( β = −0.05, standard error = 0.02, p = .030), whereas no associations between the negative affectivity by social inhibition interaction term with OCT indices were found. Conclusions: The results suggest that plaque characteristics in Type D have more features of plaque vulnerability. The negative affectivity component seems to drive the associations between Type D and vulnerable plaques. These findings provide new insights into the mechanism involved in the association between Type D and major adverse cardiac event.